Legal Protection for Consumers on Online Trade of Imported Food Products That Do Not Have a Circulation License in Indonesia - Maswandi; Jamillah; Widyawati Anggresia Manihuruk (Budapest International Research and Critics University, 2021)
Legal protection for consumers for online trading of imported food products without a distribution permit is something that is very important to do in Indonesia, considering that for consumers to obtain any goods through buying and selling is not something difficult in the era of modern technology at this time with the presence of online media, but maintaining the health of certain food products is the main goal for everyone. The presence of online media makes it easier for consumers and business actors to access buying and selling transactions. The online media that are widely used by business actors include Instagram, Facebook, WhatsApp and so on. However, the existence of several products in the form of imported food without a distribution permit sold online from business actors will certainly have a negative impact on consumers as buyers, especially the impact on health caused by food products. Although Law no. 8 of 1999 concerning Consumer Protection can be used as an umbrella to provide protection for consumers. However, considering that the regulation does not stipulate a supervisory mechanism for business actors who do not have a distribution permit, so that the legal protection that is implemented cannot run properly as determined, that's why there are still many business actors in trading imported food products that do not yet have a license. distribution permit which ultimately does not provide legal protection for consumers properly is the cause of the weak regulation on consumer protection.